Bilbliometric Analysis of Euthanasia in the Perspective of Medical Ethics - Yuniarti, Elsa; Jessi Rizkanauli Simangunsong; Aditiya Ramadhani; Nabila Azzahra (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Euthanasia has emerged as a critical topic of debate in society, encompassing both public discourse and private considerations within medical, legal, and ethical domains. The concept, which involves death with or without physician assistance, has gained significant attention due to its complex implications for human rights, medical ethics, and professional practice. The development of euthanasia policies in various countries has raised new challenges related to conscientious objection and medical practice adjustments. Methods: This study employed a bibliometric analysis approach using Scopus as the primary data source. The search query focused on